Microplastic Pollution in Green Shells in Aquatic Ecosystems: A Literature Review of Determinant Factors and Management - Globila Nurika; Hilda Nur Abidah; Farida Wahyu Ningtyias; Edza Aria Wikurendra (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Water territories produce a large number of biota worldwide. The imbalance in conserving aquatic ecosystems, along with the increasing disposal of waste into the environment, has resulted in the risk of contamination of the environment and the resulting biota. The dangers of waste disposal into water can destroy the ecosystem and affect the usability of water for the environment and human beings. Discussion: The PRISMA method was used in this literature review, which examined 35 articles: 23 articles from ScienceDirect, 10 articles from Proquest, and 2 articles from PubMed. Data were analyzed by synthesizing the research variables compared with theory and then presented in the form of tables and figures. The results of this study are presented with a complete narrative description of three sub-discussions, which consisted of the characteristics of microplastics in green mussels (color, shape, size, and abundance). The color was acquired in the dark, with the predominant form of fibers <1 mm in size, which determined the amount of microplastics in green mussels induced by both human and industrial activities, as well as countermeasures through filtration of industrial effluents, the utilization of organic plastics, and policy enforcement. Conclusion: Microplastics found in green mussels in Asian waters vary in their characteristics, with the main determinants of human and industrial activities as well as multi-sectoral countermeasures.